Effect of an Infertility Counseling Education Program on Education Satisfaction and Counseling Competency of Nurses - Jummi Park PhD, MSN, RN; Nayeon Shin PhD, MSN, RN (SAGE Publishing, 2021)
The purpose of this study is to investigate the effects of an infertility counseling education program on education satisfaction and counseling competency of nurses. The study used a one-group pretest-posttest design. Participants were 135 nurses in Korea. Data on demographic characteristics on education satisfaction, and counseling competency were collected. After participating in the infertility counseling education program, the level of counseling competency increased significantly over that before participating in the infertility counseling education program. The infertility counseling education program improved the counseling competency of the participating nurses. Use of such an infertility counseling education program is recommended when nurses counsel patients facing infertility. It is necessary to repeat this study in the future to clarify the effects of these counseling education programs.